Produtividade e nutrição do capim Marandu adubado com fosfatos e óxidos de cálcio e magnésio - Cinthya Souza Santana (2015)
Among the sources of calcium (Ca) and magnesium (Mg) there has been an increase in the use of calcium and magnesium oxides in agricultural activities. However, little is known about the effects on the soil acidity parameters, supply of Ca and Mg to plants as well as possible influences on the availability of phosphorus (P) in the soil and its availability for plants. Thus, the aim of this study was to evaluate changes in the soil chemical properties, in the production and nutrition of Brachiariabrizantha cv. Marandu by applying calcium and magnesium oxide as calcium and magnesium sources and two sources of phosphorus. The experiment was conducted in a greenhouse at Instituto de Ciências Agrárias, from UFMG (Institute of Agricultural Sciences, UFMG). The design was completely randomized in a factorial arrangement (5x2) with three replications which consisted of five doses of calcium and magnesium oxide (0, 200, 400, 800 and 1200 kg ha-1), two sources of phosphorus (Bayovar phosphate rock - FN and superphosphate - SS). During cultivation, the forages were irrigated with distilled water and the nutritional requirements were supplied with coverage fertilizers of 50 mg dm-3of nitrogen and 20 mg dm-3of potassium applications. Four sections were performed, the first 70 days after planting and the following three every 35 days. In each section the following features were evaluated: height, number of tillers, dry matter of the aerial part (DMAP), soil and leaves chemical characteristics. In the last section, roots were collected to determine the root dry matter (RDM). The highest oxide dose applied provided the highest Ca and Mg available in the soil. The effect of applying Ca and Mg oxide in the production of DMAP, RDM, plant height and tillering of Marandu grass were higher when associated with the SS. The best productivity responses and nutrition of Marandu grass when fertilized with the FN were observed in the absence of Ca and Mg oxide application.